The Role of Vitamin D in Preventing Root Resorption - Implications for Different Orthodontic Appliances - Tsai, Hsun-Hui (Archive of Orofacial Data Science, 2025)
AIM: This literature review evaluates the influence of vitamin D on external apical root resorption (EARR), orthodontic tooth movement rate, and associated complications, with consideration of orthodontic appliance design. METHODS: A structured search was conducted using PubMed databases for clinical studies published before February 2025. Nineteen studies were included, involving various orthodontic appliances and vitamin D administration routes. RESULTS: Vitamin D, especially when locally injected, was associated with accelerated tooth movement and a potential reduction in EARR. However, results were not consistently statistically significant. Appliance design influenced outcomes: self-ligating systems and clear aligners showed lower EARR incidence compared to conventional brackets, likely due to reduced force magnitude and improved control. CONCLUSION: Vitamin D may positively regulate orthodontic tooth movement and root resorption, though effects vary by biological and mechanical context. Appliance selection and force application strategies remain critical in minimising adverse effects and optimising outcomes.